2012
DOI: 10.1080/03650340.2012.695863
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic fertilizers made from slaughterhouse wastes on yield of crops

Abstract: Possible agricultural utilization of four different processed slaughterhouse waste composts and meat powder was examined in a field experiment in 2002-2008. The trial was set up with different crops on a calcareous sandy soil. The site was prone to drought. The soil was weakly supplied with N, P and K. Composts were applied once at five levels (0, 25, 50, 100, 200 t ha 71 fresh compost and 0, 2.5, 5.0, 10, 20 t ha 71 meat powder) in four replications. The fertilizing effect of these byproducts was pronounced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…in Hungary (Ragályi and Kádár, 2012). The hazardous slaughterhouse waste became a nonhazardous product following heat treatment making soil application possible (Ragályi and Kádár, 2012). Slaughterhouse waste compost was applied to sugar beet ( Beta vulgaris L. var.…”
Section: Introductionmentioning
confidence: 99%
“…in Hungary (Ragályi and Kádár, 2012). The hazardous slaughterhouse waste became a nonhazardous product following heat treatment making soil application possible (Ragályi and Kádár, 2012). Slaughterhouse waste compost was applied to sugar beet ( Beta vulgaris L. var.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, PM addition did not affect maize yield satisfactorily as reported by Busari et al [116]. On the other hand, Ragályi and Kádár [54] preferred fertilization with composted cattle waste (CCW) at a 25-50 t ha −1 application rate instead of chemical use for higher triticale production in Hungary. After three years, Nunes et al [44] cultivated soybean and maize plants with the same fertilizer at different dosages (0, 4, 8, 12 and 16 t ha −1 ) and found a quadratic relationship between the crop yield and fertilization rate.…”
Section: Dose Calculation and Yield Potential Assessmentmentioning
confidence: 69%
“…Authors reported 0.2 to 0.5 t ha −1 productivity, which was higher than the control as well as urea-treated residual plots. Ragályi and Kádár [54] provided evidence of greater residual fertility in soils treated with CCW even after 3-4 years of cultivation. Recently, Bhunia et al [15] proved that dried animal waste was residually more efficient than the soils treated with chemical fertilizers and market available vermicomposts.…”
Section: Dose Calculation and Yield Potential Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common method used to repurpose slaughterhouse waste involves their conversion by rendering plants into industrial byproducts such as fats and oils, in the form of lard and tallow (Chakraborty et al, 2014), fertilizers derived from organic compost (Darch et al, 2019), biogas through methane production (Ware and Power, 2016), and animal feed as meat powder (Ragályi and Kádár, 2012), as shown in Figure 1. Yet, given stricter regulations on the processing of carcasses, rendering has become costly (Franke-Whittle and Insam, 2013).…”
Section: Introductionmentioning
confidence: 99%